Transition‐Metal‐Free Visible Light‐Induced Imino‐trifluoromethylation of Unsaturated Oxime Esters: A Facile Access to CF3‐Tethered Pyrrolines. Issue 9 (6th August 2021) - Chen, Bin; He, Han; Xu, Jiawei; Guo, Kang; Xu, Ning; Chen, Kang; Zhu, Yingguang
Abstract: A novel transition‐metal‐free iminotrifluoromethylation of unsaturated oxime esters has been achieved through Rhodamine B photoredox catalysis under mild conditions. This methodology provides facile access to various CF3 ‐tethered pyrroline derivatives in high efficiency. The gram‐scale reaction demonstrates the potential value of this protocol in organic synthesis. Abstract : The first example of iminotrifluoromethylation of unsaturated oxime esters was achieved through Rhodamine B catalysis under transition‐metal‐free conditions. This transformation provides facile access to CF3 ‐tethered pyrrolidines under mild conditions.